2017
DOI: 10.1108/apjml-06-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer’s showrooming behaviour

Abstract: Purpose Recent multichannel research suggests that consumers use multiple channels to reap attribute-based benefits which have led to showrooming phenomenon. The purpose of this paper is to investigate the reasons for consumers’ showrooming behaviour and propose a comprehensive model based on application and extension of the “Theory of planned behaviour”. Design/methodology/approach Using the probability sampling approach, 278 complete responses were obtained via web-based surveys for analysing the showroomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 96 publications
(173 reference statements)
2
33
0
1
Order By: Relevance
“…Showrooming has consistently been related to the motivation of finding lower prices online [5]. The literature has confirmed that price-consciousness is an individual psychographic factor that positively affects the attitude and intentions of showrooming [30,56]. In a qualitative study, Fiestas and Tuzovic (2021) [2] argued that getting the best value is a benefit sought by showroomers.…”
Section: Value Consciousnessmentioning
confidence: 98%
“…Showrooming has consistently been related to the motivation of finding lower prices online [5]. The literature has confirmed that price-consciousness is an individual psychographic factor that positively affects the attitude and intentions of showrooming [30,56]. In a qualitative study, Fiestas and Tuzovic (2021) [2] argued that getting the best value is a benefit sought by showroomers.…”
Section: Value Consciousnessmentioning
confidence: 98%
“…"Better Online Service Quality" and "Lower Prices Online" induced customers to later purchase online. Price conscious customers and those with the ability to use multiple channels were more likely to engage in showrooming behavior (Arora et al, 2017). Despite the growing popularity of consumers adopting m-shopping activities and the increasing academic attention, consumer m-shopping utilization remains low and research of its causes remains in its infancy (Marriott et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, we include this variable in our study. Multichannel self‐efficacy (consumers' ability and confidence to use multiple channels) and switching costs can moderate the effect of external search and attractiveness of alternate channels on switching intentions (Arora, Singha, & Sahney, 2017; Li et al, 2018). Hence, we examine the moderating effect of multichannel self‐efficacy and switching costs on the relationship between (a) extent of information search and cross‐channel switching intentions, (b) alternative attractiveness and cross‐channel switching intentions.…”
Section: Introductionmentioning
confidence: 99%